2008
DOI: 10.1177/0042098008098204
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Insecure in Large Housing Estates: Tackling Unsicherheit in the Risk Society

Abstract: The aim of this paper is to analyse Zygmunt Bauman's three-part concept of Sicherheit (safety, certainty and security) in the specific context of large housing estates in Amsterdam (the Netherlands) and Milan (Italy). The efficacy of the different actions and policies, which seek to tackle unsafety, uncertainty and insecurity will be qualified on the basis of their correspondence and potential to face the various dimensions of Sicherheit. In both Amsterdam and Milan, there is a weak connection between the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 16 publications
(14 reference statements)
3
29
0
Order By: Relevance
“…Our work is situated in the context of wider debates about how the mass media contribute to the stigmatising of the socially excluded and the places in which they live (see Bullock et al, 2001;Devereux et al, 2011aDevereux et al, , 2011bGolding and Middleton, 1982;Hayward and Yar, 2006: 11-12;Lens, 2002). Influenced largely by Goffman (1963), who understood stigma as 'spoiled identity', an important body of research (see Bauder, 2002;Blokland, 2008;Greer and Jewkes, 2005;Hastings, 2004) has identified how the mass media and other social forces construct and unquestioningly reproduce sensationalised negative stereotypes, which damage the reputations of the places in which the poor live, a process that results in certain neighbourhoods suffering from endogenous stigmatisation (see Aalbers and Rancati, 2008;Gourlay, 2007;Oresjo et al, 2004;Palmer et al, 2004;Warr, 2006;Wassenberg, 2004). These stigmatisation processes are complex and affect the perspectives of both those inside and outside such places (Warr, 2005).…”
Section: Stigmatising Poor People and Placesmentioning
confidence: 99%
“…Our work is situated in the context of wider debates about how the mass media contribute to the stigmatising of the socially excluded and the places in which they live (see Bullock et al, 2001;Devereux et al, 2011aDevereux et al, , 2011bGolding and Middleton, 1982;Hayward and Yar, 2006: 11-12;Lens, 2002). Influenced largely by Goffman (1963), who understood stigma as 'spoiled identity', an important body of research (see Bauder, 2002;Blokland, 2008;Greer and Jewkes, 2005;Hastings, 2004) has identified how the mass media and other social forces construct and unquestioningly reproduce sensationalised negative stereotypes, which damage the reputations of the places in which the poor live, a process that results in certain neighbourhoods suffering from endogenous stigmatisation (see Aalbers and Rancati, 2008;Gourlay, 2007;Oresjo et al, 2004;Palmer et al, 2004;Warr, 2006;Wassenberg, 2004). These stigmatisation processes are complex and affect the perspectives of both those inside and outside such places (Warr, 2005).…”
Section: Stigmatising Poor People and Placesmentioning
confidence: 99%
“…Previous research on these themes has examined how mass media and other social forces contribute to the creation of negative stereotypes, which damage the reputations of the places in which the underclass or poor reside (Bauder, 2002;Blokland, 2008;Greer and Jewkes, 2005;Hastings, 2004). Negative and sensationalist media coverage of poor neighbourhoods is consistently referred to in studies which attempt to explain how neighbourhoods come to suffer from endogenous stigmatization (Aalbers and Rancati, 2008;Gourlay, 2007;Oresjo et al, 2004;Palmer et al, 2000;Warr, 2006;Wassenberg, 2004). The existing research literature demonstrates that negative reputations of such places can, in themselves, have a profound effect on the life chances, experiences and self-image of those who live in neighbourhoods which carry a stigma (Permentier et al, 2007(Permentier et al, , 2008(Permentier et al, , 2009).…”
Section: Stigmatizing Placesmentioning
confidence: 99%
“…It can incorporate aspects such as security, risk, comfort and well‐being, to mention just some interpretations. In many cases experiences of safety are distinct from the actual risk of being the object of crime or accidents, often referred to as objective safety (Aalbers & Rancati 2008). However, it is well‐established that experienced or subjective safety does not need to correspond to objective risks (see e.g.…”
Section: Safety In Residential Areasmentioning
confidence: 99%
“…However, it is well‐established that experienced or subjective safety does not need to correspond to objective risks (see e.g. Koskela 1997; Aalbers & Rancati 2008). In this paper, safety refers to when an individual feels comfortable and not worried or fearful.…”
Section: Safety In Residential Areasmentioning
confidence: 99%